Digitalization of Islamic Philanthropy: Development of a Philanthropic Da’wah Model rumahzakat.org - Hamdani, Amin; Aziz, Malik Akbar Abdul (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This research investigates the development of the rumahzakat.org philanthropic da'wah model and developing activities in the digital world. This study aims to explore, study and discover the philanthropic da'wah model developed by rumahzakat.org. This research was conducted using a qualitative approach and a case study. His research processes include observations, in-depth interviews, examination of digital and manual documents, and data analysis. This research found that the rumahzakat.org institution uses the da'wah bil hal or da'wah amali model to encourage people to carry out various charitable activities. This institution managesÂ zakat,Â infaq, shadaqah, and other social funds to promote community empowerment activities based on love for others. Apart from that, the results show that philanthropic da'wah activities using new media are da'wah activities that build relationships with the media in the form of consolidation, namely mutual benefit for each other's goals. Finally, the results show that rumahzakat.org can carry out digital-based philanthropic da'wah activities to adapt da'wah activities to current developments, make program services more accessible, and make services available transparently to everyone. To develop a transformative da'wah model, da'wah based on digital philanthropy must be improved.